2011
DOI: 10.1002/ana.22311
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers for Parkinson disease diagnosis and progression

Abstract: Background There is a clear need to develop biomarkers for Parkinson disease (PD) diagnosis, differential diagnosis of parkinsonian disorders, and monitoring disease progression. We and others have demonstrated that a decrease in DJ-1 and/or α-synuclein in the cerebrospinal fluid (CSF) is a potential index for PD diagnosis, but not for PD severity. Methods Using highly sensitive and quantitative Luminex assays, we measured total tau, phosphorylated tau, amyloid beta peptide 1-42 (Aβ1-42), Flt3 ligand and fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
377
13
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 383 publications
(426 citation statements)
references
References 54 publications
(121 reference statements)
27
377
13
9
Order By: Relevance
“…The measurement of a‐syn concentrations in CSF by ELISAs has been proposed as a biomarker for a‐syn‐related disorders. However, despite many studies showing a reduction in CSF a‐syn levels in PD and in DLB,4, 6 overall results are not consistent 7. Even in those studies where a reduction in CSF a‐syn has been demonstrated, the differences are small8 and there is considerable overlap within patient groups and between patient and control groups.…”
Section: Introductionmentioning
confidence: 96%
“…The measurement of a‐syn concentrations in CSF by ELISAs has been proposed as a biomarker for a‐syn‐related disorders. However, despite many studies showing a reduction in CSF a‐syn levels in PD and in DLB,4, 6 overall results are not consistent 7. Even in those studies where a reduction in CSF a‐syn has been demonstrated, the differences are small8 and there is considerable overlap within patient groups and between patient and control groups.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, these changes are not disease specific, being shared by many neurodegenerative diseases. A recent study, carried out in a large cohort including PD (n. 126), MSA (n. 32), AD (n. 50), and controls (n. 137), showed significantly lower CSF levels of the cytokine Flt3 ligand in MSA patients as compared to PD subjects (Shi et al, 2011).…”
Section: Inflammation and Glial Activationmentioning
confidence: 95%
“…These findings have lead to a revision of the National Institute of Neurological Disorders and Stroke-Alzheimer Disease and Related Disorders (NINCDS-ADRDA) criteria for the diagnosis of AD including CSF biomarkers (Dubois et al, 2007). Studies report normal CSF levels of tau and phosphorylated tau in PD (Blennow et al, 1995;Parnetti et al, 2008;Alves et al, 2010;, whereas unchanged or slightly decreased levels of A 1-42 have been reported (Sjögren et al, 2002;Mollenhauer et al, 2006;Bibl et al, 2006;Parnetti et al, 2008;Compta et al, 2009;Alves et al, 2010;Siderowf et al, 2010;Montine et al, 2010;Leverenz et al, 2011;Shi et al, 2011). More recently, several studies have been published reporting a possible association between low A 1-42 levels and cognitive impairment in PD (Compta et al, 2009;Alves et al, 2010;Siderowf et al, 2010;Montine et al, 2010;Leverenz et al, 2011).…”
Section: Classical Csf Biomarkers and Risk Of Cognitive Impairment In Pdmentioning
confidence: 99%
“…Shi and coworkers measured total tau, phosphorylated tau, Aβ peptide 1-42 [Aβ (1-42)], Flt3 ligand, and fractalkine levels in CSF in a large cohort of PD patients at different stages, as well as in healthy and diseased controls, and found that the ratio of phosphorylated-tau/tau can be used to distinguish PD from MSA (a disease that overlaps with PD clinically). Moreover, with the CSF Flt3 ligand, PD could be clearly differentiated from MSA with an excellent sensitivity (99%) and specificity (95%) [26]. Furthermore, the authors identified CSF fractalkine/Aβ (1-42) as positively correlated with PD severity in cross-sectional samples, as well as with PD progression in longitudinal samples [26].…”
Section: Tau and Othersmentioning
confidence: 99%
“…Correlated with PD severity [14] [9] α-Synuclein↓ [7,22] 71% sensitivity and 53% specificity patients with PD vs. controls, DLB, and MSA [22] Phosphorylated α-synuclein↑ [21,23] No correlation between the α-synuclein level and PD severity [7,19,22,24] Antibody towards monomeric α-synuclein↑ [25] Tau Total tau↓ [26] Distinguish Patients with low UA levels in serum may be more prone to developing PD, and an inverse relationship between UA and severity of PD was robust for men but weak for women [11]. Another study in the Chinese population reported similar results, which suggests that the serum UA level could be a useful biomarker of PD diagnosis and disease progression [12].…”
Section: ↑[14]mentioning
confidence: 99%